Effects of six compost products on soil organic carbon and nitrogen levels in alfisol, rice yields, and diazotrophic endophytic populations - Cahyani, Vita Ratri (2025)
The decrease in nutrient content in the soil occurs because of an imbalance between nutrient intake and loss. This study aimed to evaluate the effect of applying six types of compost products, with different compost materials and bioactivators, on the soil organic carbon (SOC) and total nitrogen (TN) levels in Alfisol, on rice yields, and diazotrophic endophytic populations. The pot experiment was arranged in a Completely Randomized Design with a single factor consisting of 10 levels and 3 replications. The treatments compared control (R0), 6 types of compost (R1-R6), 50% chemical fertilizer (CF) (R7), 100% CF (R8), and a set combination (R9). Rice with a variety of Mentik Wangi was grown and harvested on 118 DAP. The results showed that the treatment R5 (compost C4 of a mixture of leaf litter, cow dung, peanut plant residue, and rock phosphate with bioactivator RMC) gave the highest increases of SOC and TN by 200% and 228.57%, and the highest plant dry weight and total seed weight by 247.55% and 171.16% compared to the control, respectively. Three treatments of R4 (compost C3), R6 (compost C5), and R9 (50% dosage of compost C3 in combination with mycorrhiza, zeolite, Azolla, and rock phosphate) yielded a similar effect at the second-highest levels in increasing SOC, TN, and rice yields. There was no significant effect of treatments on the population of diazotrophic bacterial endophytes in rice leaves. The present study revealed that compost enrichment with an effective bioactivator contributed significantly higher effects on soil fertility, plant growth, and yield compared to 100% chemical fertilizer (R8).